Disparities in colon cancer survival by insurance type: a population-based analysis - Pulte, Dianne; Jansen, Lina; Brenner, Hermann (Diseases of the colon & rectum, 2018)
BACKGROUND: Colon cancer is a common cancer with a relatively high survival for nonmetastatic disease if appropriate treatment is given. A lower survival rate for patients with no or inadequate insurance has previously been documented, but the differences have not been explored in detail on a population level. OBJECTIVE: The purpose of this study was to examine survival for patients with colon cancer by insurance type. DESIGN: Complete analysis was used to examine 1-, 2-, and 3-year survival rates. SETTINGS: This was a population-level analysis. PATIENTS: Patients were drawn from the in-patients diagnosed with colon cancer at ages 15 to 64 years between 2007 and 2012 in the Surveillance, Epidemiology, and End Results 18 database by insurance type (Medicaid, uninsured, or other insurance) MAIN OUTCOME MEASURE:: This study measured overall survival. RESULTS: A total of 57,790 cases were included, with insurance information available for 55,432. Of those, 7611 (13.7%), 4131 (7.5%), and 43,690 (78.8%) had Medicaid, no insurance, or other insurance. Patients with Medicaid or without insurance were more likely to have metastatic disease compared with those with other insurance. Survival was higher for patients with insurance other than Medicaid, with 3-year survival estimates of 57.0%, 61.2%, and 75.6% for Medicaid, uninsured, and other insurance. Significant disparities continued to be observed after adjustment for stage, especially for later-stage disease. When only patients with stage I to II disease who had definitive surgery and resection of ≥12 lymph nodes were included in the analysis, the discrepancy was decreased, especially for uninsured patients. LIMITATIONS: Information on chemotherapy use and biological markers of disease severity are not available in the database.CONCLUSIONS: Colon cancer survival is lower for patients with no insurance or with Medicaid than for those with private insurance. Differences in rates of definitive surgery and adequate lymph node dissection explain some of this disparity. See Video Abstract at http://links.lww.com/DCR/A585.